THE DEVELOPMENT OF PUBLIC LAW IN THE POSTMODERN ERA: IDEALISM AND REALITY IN A DEMOCRACY (World Economics and Finance Bulletin, 2025)
The research deals with the relationship between the development of public law and the impact of postmodern philosophy on its democratic principles. Public law is characterized by its flexibility derived from judicial precedents, which makes it able to adapt to changes . The paper explores the idealism inherent in common law, which is seen as a tool for protecting individual rights and promoting justice through precedentbased judicial decisions, and is supposed to be independent of political pressures, which These challenges are embodied in cases such as the US Supreme Court’s ruling in Obergefell v. Hodges (2015) that legalized same-sex marriage, which reflected the evolution of values but raised controversy about judicial overreach of legislative will . The research proposes solutions to achieve a balance between idealism and reality, such as incorporating legal pluralism, enhancing transparency in the judiciary, and cooperating with legislators to keep up with developments. It concludes that public law needs to redefine its role